Sarcoidosis and risk of venous thromboembolism: A systematic review and meta-analysis - Patompong Ungprasert (2018)
© Mattioli 1885. Background: Several chronic inflammatory disorders, such as rheumatoid arthritis, inflammatory myositis and systemic lupus erythematosus, have been linked to an increased risk of venous thromboembolism (VTE). However, the data on sarcoidosis is unclear. Objectives: To evaluate the risk of VTE among patients with sarcoidosis. Methods: We conducted a systematic review and meta-analysis of observational studies that reported odds ratio, relative risk, hazard ratio or standardized incidence ratio comparing risk of VTE in patients with sarcoidosis versus non-sarcoidosis participants. Estimated effects were extracted from each study and were pooled together using the random-effect, generic inverse variance method of DerSimonian and Laird. Result: Out of 772 potentially relevant articles, three eligible studies were identified and included in the data analysis. The pooled risk ratio of VTE in patients with sarcoidosis was 1.42 (95% CI, 1.12-1.79). The statistical heterogeneity of this study was moderate with an I2 of 72%. Conclusion: Our study demonstrated a statistically significant increased VTE risk among patients with sarcoidosis.